Intrathecal 2-Chloroprocaine 3% Versus Hyperbaric Bupivacaine 0.75% for Cervical Cerclage: A Double-Blind Randomized Controlled Trial. (March 2022) - Lee, Allison; Shatil, Ben; Landau, Ruth; Menon, Prahlad; Smiley, Richard
Abstract : BACKGROUND: Cervical cerclage is a short ambulatory procedure. For spinal anesthesia, local anesthetic agents with rapid postoperative resolution are desired. We hypothesized that in combination with fentanyl, intrathecal 2-chloroprocaine would produce earlier resolution of motor block, resulting in shorter time to meet recovery room discharge criteria than hyperbaric bupivacaine. METHODS: Women undergoing cervical cerclage with spinal anesthesia were randomized to receive intrathecal 2-chloroprocaine 3% 50 mg or hyperbaric bupivacaine 0.75% 9 mg, both with fentanyl 15 µg. Doses were empirically selected. The onset and resolution of sensory and motor blockade and time to achieve recovery room discharge criteria were monitored. On postoperative day 1, patients rated their satisfaction with the anesthetic and reported on transient neurologic symptoms (TNS), back pain, or headache. The primary outcome was time from spinal injection to motor block resolution. The main secondary outcomes included times from spinal injection to (i) T12 dermatomal level, (ii) sensory block resolution, and (iii) ability to ambulate and void. RESULTS: Forty-three women were enrolled and randomized to either the chloroprocaine (N = 23) or bupivacaine group (N = 20). The mean (standard deviation [SD]) duration of surgery was 35.3 (11.4) minutes. There was no difference between groups for time to motor block resolution—the median [interquartile range] time for the bupivacaine group (N = 17) was 112 [97–143] minutes versus 109 [88–148] minutes in the chloroprocaine group (N = 22), P = .66, but there was a significant difference in median time to sensory block resolution: 143 [116–162] minutes in the chloroprocaine group versus 198 [152–263] minutes in the bupivacaine group, P = .002. The recovery room discharge criteria, which at our institution include the ability to ambulate unassisted and void urine, were met 76 (95% CI, 33–145) minutes earlier in the chloroprocaine group, P < .0005. One complete block failure occurred with hyperbaric bupivacaine and 2 subjects in each group received treatment for intraoperative discomfort. No patients reported TNS. CONCLUSIONS: Intrathecal 2-chloropocaine 3% provided similarly effective surgical anesthesia for cerclage placement. Although no difference in time to motor block resolution between groups was observed, the time to sensory block resolution and time to meet recovery room discharge criteria were both significantly shorter among patients who received chloroprocaine than patients who received bupivacaine. Future studies are needed to identify and compare equipotent doses of chloroprocaine and bupivacaine to confirm the superiority of chloroprocaine for this ambulatory obstetric procedure.